(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The history of the emergence of gender studies in foreign linguistics is presented. Various approaches, within the framework of which gender studies are currently being developed, are considered. The class "gender" regarded in linguistics surprisingly recently, extremely later than in different sciences. The prehistory of gender research in linguistics is rooted in antiquity, whilst the knowledge of the kinds of herbal intercourse (sexus) and grammatical gender (gender) began, and the symbolic-semantic idea of the class of gender (genus) regarded, thinking about it in near reference to on the spot reality: the presence human beings of various intercourse.